Measles outbreak amongst Manymar population of Jeddah City, Saudi Arabia - Al-Abdullah, Nabeela Abdullah (International Journal Of Community Medicine And Public Health, 2018)
Background: Worldwide efforts for measles elimination are made possible due to the availability of a highly effective measles vaccine. In spite of a highly vaccinated population, an outbreak of measles has occurred in Jeddah province of Saudi Arabia, from January to February 2018. Methods: An outbreak investigation was conducted to describe the epidemiology of the outbreak. A performance audit of the control measures taken by the primary healthcare team was carried out in accordance with the World Health Organization (WHO) standards. Results: Of the 31 cases reported, the patient’s ages range from 1–9 years with an average age of 6 (±2) years. The index case was a 9 year old male. The performance indicator target for outbreak control measures was achieved. Ninety percent of the cases were investigated within 48 hours. Specimens such as serum blood and nasopharyngeal swabs were collected within the optimal period to test for measles IgG and IgM antibody. Conclusions: This outbreak demonstrates the increased susceptibility of unvaccinated children aged 6–11 months. To prevent possible future outbreaks, community awareness through educational campaigns, a review of children’s vaccination records, enhanced community surveillance and a measles ‘catch-up’ mass immunization campaign to interrupt chains of transmission are necessary.